“You're Really Gonna Kick Us All Out?” Sustaining Safe Spaces for Community-Based HIV Prevention and Control among Black Men Who Have Sex with Men - Garcia, Jonathan (PLoS One, 2015)
Black men who have sex with men (BMSM) experience among the highest rates of HIV infection in the United States. We conducted a community-based ethnography in New York City to identify the structural and environmental factors that influence BMSMs vulnerability to HIV and their engagement with HIV prevention services. Methods included participant observation at community-based organizations (CBOs) in New York City, in-depth interviews with 31 BMSM, and 17 key informant interviews. Our conceptual framework shows how creating and sustaining safe spaces could be a critical environmental approach to reduce vulnerability to HIV among BMSM. Participant observation, in-depth and key informant interviews revealed that fear and mistrust characterized men’s relation to social and public institutions, such as churches, schools, and the police. This fear and mistrust created HIV vulnerability among the BMSM in our sample by challenging engagement with services. Our findings suggest that to be successful, HIV prevention efforts must address these structural and environmental vulnerabilities. Among the CBOs that we studied, “safe spaces” emerged as an important tool for addressing these environmental vulnerabilities. CBOs used safe spaces to provide social support, to address stigma, to prepare men for the workforce, and to foster a sense of community among BMSM. In addition, safe spaces were used for HIV and STI testing and treatment campaigns. Our ethnographic findings suggest that safe spaces represent a promising but so far under-utilized part of HIV prevention infrastructure. Safe spaces seem integral to high impact comprehensive HIV prevention efforts, and may be considered more appropriately as part of HIV capacity-building rather than being nested within program-specific funding structures.